72x-9=20x+30
72x-20x=30+9
52x=39
x=39/52
x=3/4=0.75
2006-12-06 09:38:46
·
answer #1
·
answered by niel_alinda 3
·
0⤊
0⤋
9(8x-1)=5(4x+6)
9*8x + 9*-1 = 5*4x + 5*6 "*" means Multiply
72x - 9 = 20x + 30
72x = 20x + 39 (-9 is brought right hand side and becomes +9)
52x = 39 (20x is brought LHS and becomes -20x)
x = 39/52
x = 3/4 (More simplified answer)
You can check the answer by inputing the x value in the main equation.
9(8x-1)=5(4x+6)
9(8*39/52 - 1) = 5(4*39/52 + 6)
45 = 45
Therefore it proofs that our answer is correct.
2006-12-06 09:48:24
·
answer #2
·
answered by prashmanic 4
·
0⤊
0⤋
I got....... 9(8x-1)=5(4x=6)
72x-9=20x+30
72x=20x+39
52x=39
x=39/52 or 0.75
2006-12-06 11:18:49
·
answer #3
·
answered by angelbaby4always 2
·
0⤊
0⤋
multiply the function
72x - 9 = 20x +30
-20X +9 -20x +9
get like terms on same side
52X = 39
divide by 52
X= 39/52= 3/4= .75
2006-12-06 09:40:58
·
answer #4
·
answered by ۞ JønaŦhan ۞ 7
·
0⤊
0⤋
9(8x-1)=5(4x+6)
[multiply through]
72x-9=20x+30
[add 9 to both sides]
72x=20x+39
[subtract 20x from both sides]
52x=39
[divide by 52]
x=39/52=3/4=0.75
2006-12-06 09:40:02
·
answer #5
·
answered by Gary K 2
·
0⤊
0⤋
72x-9=20x+30
52x = 39
x = 39/52
2006-12-06 09:37:30
·
answer #6
·
answered by asndude7 2
·
0⤊
0⤋
72x-9=20x+30
adding -20x+9
52x=39
dividing by 52
x=(39/52)
reducing by dividing by 13
x=3/4
2006-12-06 09:38:12
·
answer #7
·
answered by raj 7
·
0⤊
0⤋
72x-9=20x+30
52x=39
x=39/52
x=3/4
2006-12-06 09:39:17
·
answer #8
·
answered by Anonymous
·
0⤊
0⤋
72x-9 = 20x+30
52x=39
x=.75
2006-12-06 09:47:02
·
answer #9
·
answered by ryan c 2
·
0⤊
0⤋
72x-9=20x+30
72x=20x+39
52x=39
x=39/52
x=3/4
2006-12-06 09:39:39
·
answer #10
·
answered by L_Bizzy25 2
·
0⤊
0⤋